The life course of adult males with attention deficit hyperactivity disorder - Imperio, Diana S. (Animo Repository, 2008)
This study examined the life course of male adults with Attention Deficit Hyperactivity Disorder (ADHD) and compared it with those of normal young adults. A total of 10 single males aged 25-35 were gathered for this research, and were divided into two groups: those with ADHD and those without the condition. Using life review charts and interviews, themes about the participants’ work experiences and love relationships were identified and compared. In terms of work experiences of adults with ADHD, results revealed that they frequently change jobs and have variety of work interests and activities. Adults without ADHD have stable work status and satisfying work relationships. In terms of love relationships, adults with ADHD have brief and simultaneous encounters with their love prospects. Adults without ADHD, on the other hand, have the following themes: enduring relationships and delay in marriage. ADHD adults and adults without ADHD both have a desire for monetary profit at work and for finding and staying with a good love partner. However, both groups are not alike in terms of their experiences about length of stay in a particular work environment, as well as their views about marriage and commitment.